Asuhan Kebidanan Komprehensif pada Ny. N di Klinik Pratama BKIA Rakyat - Jumasia, Jumasia; Masnilawati, Andi; Nurana, Sitti (Window of Midwifery Journal, 2025)
Comprehensive midwifery care is a series of health services midwives provide, starting from pregnancy, childbirth, postpartum, newborns, and family planning. The maternal mortality rate and infant mortality rate are highly dependent on the quality of health services; the higher the quality of midwives' services, the lower the maternal mortality rate and infant mortality rate. Comprehensive midwifery care can ensure that mothers and babies receive quality care throughout pregnancy until childbirth and family planning. The purpose of this study was to provide comprehensive care to Mrs. N G2P1A0, from pregnancy, childbirth, postpartum, and newborns to family planning at the Pratama BKIA Rakyat Clinic. This type of research is comprehensive, using the 7-step Varney method and documented in the form of SOAP. Based on the results obtained on Mrs. N, there were no problems and complications ranging from pregnancy, childbirth, newborn, postpartum, and family planning care provided by the authority of the midwife, and based on the client's consent.